Long-Range Stabilization of Anthrax Protective Antigen upon Binding to CMG2 - Mullangi, Vennela (American Chemical Society, 2014)
[Image: see text] Protective antigen (PA) mediates entry of edema factor (EF) and lethal factor (LF) into the cytoplasmic space of the cells through the formation of a membrane-spanning pore. To do this, PA must initially bind to a host cellular receptor. Recent mass spectrometry analysis of PA using histidine hydrogen–deuterium exchange (His-HDX) has shown that binding of the von Willebrand factor A (vWA) domain of the receptor capillary morphogenesis protein-2 (CMG2) lowers the exchange rates of the imidazole C(2) hydrogen of several histidines, suggesting that receptor binding decreases the structural flexibility of PA. Here, using His-HDX and fluorescence as a function of denaturant, and protease susceptibility, we show that binding of the vWA domain of CMG2 largely increases the stability of PA and the effect reaches up to 70 Å from the receptor binding interface. We also show that the pK(a) values and HDX rates of histidines located in separate domains change upon receptor binding. These results indicate that when one end of the protein is anchored, the structure of PA is tightened, noncovalent interactions are strengthened, and the global stability of the protein increases. These findings suggest that CMG2 may be used to stabilize PA in future anthrax vaccines.